Replicate effects and test–retest reliability of quantitative sensory threshold testing in dogs with and without chronic pain. (May 2017) - Knazovicky, David; Helgeson, Erika S.; Case, Beth; Thomson, Andrea; Gruen, Margaret E.; Maixner, William; Lascelles, B. Duncan X.
Abstract: Objective: To evaluate replicate effects and test–retest reliability of mechanical and thermal quantitative sensory testing (QST) in normal dogs and dogs with osteoarthritis (OA)-associated pain. Study design: A prospective clinical study. Animals: A total of 54 client owned dogs (OA, n  = 31; controls, n  = 23). Methods: Mechanical [electronic von Frey (EVF) and blunt pressure] and thermal (hot and cold) sensory thresholds were obtained in dogs with OA-associated pain and control dogs at two visits, 7 days apart, to assess test–retest reliability. Thresholds were measured at the OA-affected joint (hip or stifle), over the tibial muscle and over the midpoint of the metatarsals. Five replicates were obtained for each modality at each site bilaterally. Results: Overall, there was no significant effect of replicates on QST response. EVF thresholds were significantly lower at the second visit in OA dogs at the affected and metatarsal sites ( p  = 0.0017 and p  = 0.0014, respectively). Similarly for control dogs, EVF thresholds were significantly lower at the second visit at the metatarsal site ( p  = 0.001). Significantly higher hot thermal latencies were seen in OA dogs at the affected and tibial testing sites ( p  = 0.014 and p  = 0.012, respectively), and in control dogs at the tibial site ( p  = 0.004). Conclusions: In QST, a replicate does not show a strong effect. However, QST results show variability over time, particularly for EVF and hot thermal stimuli. Clinical relevance: If QST is to be used clinically to evaluate a sensitized state, the variability over time needs to be accounted for in the study design.